1987
DOI: 10.1002/aoc.590010407
|View full text |Cite
|
Sign up to set email alerts
|

Organotin compounds in agriculture since 1980. Part 2. Acaricidal, antifeedant, chemosterilant and insecticidal properties

Abstract: The object of this review paper is to provide a guide to agrochemical research involving organotin compounds which has been performed since 1980. The information is presented in a tabular form and is divided into four main sections as indicated by the title. Each section is then subdivided to cover the various commercial organotin compounds. A final subsection lists investigations involving novel compounds. An additional section covers the effects of organotin agrochemicals on non-target organisms. A table of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…as additives in antifouling paints or in wood preservatives, although additional applications include their action as stabilizing agents in plastics manufacture (Crowe 1987). The toxicity of organotins depends on the number of organic groups attached to Sn and is positively correlated with both their molecular total surface area (Eng et al 1988) and their lipid solubility, which may be quantified according to octanol and water partition coefficients (Wong et al 1982;Cooney and Wuertz 1989).…”
Section: Introductionmentioning
confidence: 99%
“…as additives in antifouling paints or in wood preservatives, although additional applications include their action as stabilizing agents in plastics manufacture (Crowe 1987). The toxicity of organotins depends on the number of organic groups attached to Sn and is positively correlated with both their molecular total surface area (Eng et al 1988) and their lipid solubility, which may be quantified according to octanol and water partition coefficients (Wong et al 1982;Cooney and Wuertz 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In particular the positive ESI mass spectra of FA2 and FA3 were simpler than FA1 spectrum. In fact, the positive ESI mass spectrum of FA1 showed monomeric and dimeric sodium peaks together with other features, probably due to the formation of adducts with trimethyltin fragment ion [M+Me 3 Sn] + and NaFA adducts (such as [M+Na-FA+H] + ). The negative-ion of molecule adducts with NaFA, [M+FA] À is also observed in the spectra and support the MS assignments.…”
Section: Esi-ms Spectramentioning
confidence: 99%
“…In this context many papers, reviews and books have been published, in the past twenty years, dealing with such applications [1][2][3][4][5][6][7][8][9]. Research on the synthesis and applications of metal-based drugs are currently considered as one of the most expanding areas in biomedical and inorganic chemistry [10] and very recent studies have shown very promising in vitro cytotoxic properties of organotin compounds [11].…”
Section: Introductionmentioning
confidence: 99%
“…One drop of spore suspension (0.02 ml), prepared from 15-day-old culture, was added to the treated spots. In this way sets for o.28465 (2) o, 19923(2) -o,31 19 (1) various concentrations of the compounds were 0.2692 (2) 0.1617 (2) 0.0686 (1) prepared. The slides were left for 24 h under 0.2963 (2) 0.1506 (2) 0.5793 (1) humid conditions.…”
Section: Biological Studiesmentioning
confidence: 99%